G20 and Emerging Europe: Is There Anything Left for the EU to Do? - Vladimir Gligorov; Michael Landesmann (The Vienna Institute for International Economic Studies (wiiw), 2009)
This piece argues that three specific policy issues need to be addressed urgently in Central, Eastern and Southeastern Europe in order to avoid a sustained period of recession or depression (i) orderly exchange rate adjustment (ii) fiscal stress and (iii) financial sector vulnerability. The G-20 Declaration supports significantly the role of the IMF in the current crisis, but there is a need for an additional determined effort by the EU.
Keywords: 330